Teachers' Perceptions and Challenges on the Implementation of Online Literacy Program in JHPS 1 Muntilan - Ratri, Ayu; Budiraharjo, Markus; Kartikasari, Anita (Universitas Negeri Semarang, 2022)
Good reading skills are related to individual basic skills in achieving success and prosperity. However, reading skills in Indonesia are still low. The evidence was from the PISA results, which revealed little progress from 2015 to 2018. In tackling this problem, one of the schools in Indonesia, the Junior High Public School (JHPS) 1 Muntilan, responded it by creating Literacy Online program (henceforth LION) to support government programs. Research on reading ability has been extensively done, but no study investigates the LION program. Therefore, this study aimed to discover the perceptions and challenges of teachers who have a pivotal role in the success of the LION program at JHPS 1 Muntilan. This study employed mixed-method research to get the data. The data was collected by providing a closed-ended questionnaire and interviews. The results of the study revealed that the teachers felt enthusiastic, enjoyed, affectionate, and comfortable with implementing LION. Moreover, the teachers revealed that theprogram gave a spark of hope and excitement for students toward learning autonomy. The students were found to have evolved to more actively respond to the questions following the reading materials. Accordingly, this could lead to the success of the National Assessment. Interestingly, the teachers felt overwhelmed and confused when facing passive students and had limited knowledge to give proper readings.